(untitled) - Romaniello, Stephen (Hoboken, N.J., 2006)
If you prefer to see what things look like and how to perform a task, instead of just being told, this is your ideal A to Z reference. Part I shows every Photoshop CS2 tool and how to use it. Part II provides step-by-step instructions for more than 130 key tasks and techniques. Both are arranged alphabetically and illustrated in full color. It's the ultimate Visual resource - you'll see!
Keywords: Adobe Photoshop,Computer graphics,Đồ họa vi tính